2001
DOI: 10.1111/1467-8292.00165
|View full text |Cite
|
Sign up to set email alerts
|

Identification as a Trust‐Generating Mechanism in Cooperatives

Abstract: It is commonly held that trust is a crucial mechanism for coordination and control in cooperatives. The elusive nature of trust is also emphasised. What seems to be less discussed is where trust and distrust come from, as well as the shifting conditions under which trust is developed, maintained and sometimes disposed of. This article explores one trust-making mechanism which seems to be of particular interest in cooperatives and other membership-based organisations. The mechanism in question is members' ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 12 publications
1
79
0
10
Order By: Relevance
“…Similarly, it has been shown that cooperatives are generally perceived as trustworthy, given their constraint on the profits distribution and their democratic governance (Hansmann 1996;Ole Borgen 2001). In addition, citizen ownership contributes to the trust capital of CBE initiatives and cooperatives as it provides the guarantee to non-controlling stakeholders that the firm is managed by people who share their interest (Spear 2000).…”
Section: Community-based Energy Initiatives and Institutional Resiliencementioning
confidence: 99%
“…Similarly, it has been shown that cooperatives are generally perceived as trustworthy, given their constraint on the profits distribution and their democratic governance (Hansmann 1996;Ole Borgen 2001). In addition, citizen ownership contributes to the trust capital of CBE initiatives and cooperatives as it provides the guarantee to non-controlling stakeholders that the firm is managed by people who share their interest (Spear 2000).…”
Section: Community-based Energy Initiatives and Institutional Resiliencementioning
confidence: 99%
“…Further, trust -which is seen as an important mechanism for coordination and control in co-operatives (Borgen, 2001) -can be seen as an important mediator in the idenfication-normative commitment relationship. That is, existing literature identifies elements of such a connection.…”
Section: Identification With the Coalitionmentioning
confidence: 99%
“…That is, existing literature identifies elements of such a connection. First, members do not establish reciprocal relationships without trust (Borgen, 2001). In this context trust means that the members can expect and believe that their fellow members will not withdraw their contributions to collective action when opportunities for short-term gain arise outside the coalition.…”
Section: Identification With the Coalitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farmers tend to appreciate the social links within the membership body and the fact that the co-operative constitutes a reliable trading partner (Bhuyan, 2007;Gray and Kraenzle, 1998;Österberg and Nilsson, 2009). However, it is important that they can trust their co-operatives and feel that they are being properly treated (Borgen, 2001;Hansen et al, 2002;Nilsson et al, 2009). …”
Section: Introductionmentioning
confidence: 99%